BEHAVIORAL AVOIDANCE RESPONSE OF SPRINGTAILS EXPOSED TO CONTAMINATED SOIL WITH CYPERMETHRIN COMPORTAMENTO DE FUGA DE COLÊMBOLOS EXPOSTOS A SOLOS CONTAMINADOS COM CIPERMETRINA - Zortea T.* (2015)
© 2015 Universidade Federal do Parana 1. All rights reserved.To evaluate the toxicity of cypermethrin for soil organisms is a way of understanding the effects of this drug on non-target organisms and the use of terrestrial ecotoxicology, which has standardized ISO standards for the tests, allows us to understand these effects in a closer context of a natural ecosystem. This study aims to determine the application of the effect of cypermethrin avoidance behavior of springtails of Folsomia candida species through escape behavior tests. For the tests we used a Oxisol from the western region of Santa Catarina and the Tropical Soil Artificial (SAT). The tests were conducted in a completely randomized design with five replicates. The treatments consisted of cypermethrin concentrations of 0; 7.5; 15; 22.5 and 30 mg kg-1. The number of individuals in the avoidance behavior test was analyzed by the Fisher Exact Test. Both ground natural and artificial soil were springtails escape from the lowest dose tested cypermethrin (7.5 mg kg-1) results show that the toxicity of the product used. The AC50 values for Oxisol and SAT were 8.58 mg kg-1 and 6.47 mg kg-1, respectively. Thus, the presence of cypermethrin adversely affects the F. candida behavior.